1991
DOI: 10.1139/m91-161
|View full text |Cite
|
Sign up to set email alerts
|

HT-2 toxin, roridin A, T-2 toxin, and verrucarin A mycotoxins inhibit carbon dioxide production by Kluyveromyces marxianus

Abstract: The effects of four trichothecene mycotoxins on carbon dioxide production by a yeast, Kluyveromyces marxianus, were examined. Carbon dioxide release rate was inhibited by 10% in less than 25 min or 50% in less than 65 min by 0.0625, 0.125, 1.25, and 12.5 μg/mL of verrucarin A, roridin A, T-2 toxin, and HT-2 toxin, respectively. Lower concentrations did not affect carbon dioxide release rate within 160 min. Individually, neither 0.625 μg/mL T-2 toxin nor 0.000125 μg/mL roridin A alters carbon dioxide production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
2
6
0
1
Order By: Relevance
“…Thus, when in a combination with a toxin able to inhibit growth (T‐2 toxin), even although in a concentration that alone would not affect the growth, it can cause augmentation of the inhibitory effect observed. This is in agreement with the findings of Koshinsky et al . (1991) in their study of the effects of T‐2 toxin and roridin A on carbon dioxide production by K. marxianus .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, when in a combination with a toxin able to inhibit growth (T‐2 toxin), even although in a concentration that alone would not affect the growth, it can cause augmentation of the inhibitory effect observed. This is in agreement with the findings of Koshinsky et al . (1991) in their study of the effects of T‐2 toxin and roridin A on carbon dioxide production by K. marxianus .…”
Section: Discussionsupporting
confidence: 94%
“…Little information on the effects caused by a combination of mycotoxins on yeast growth has been published. Koshinsky et al . (1991) demonstrated that a mixture of the trichothecenes T‐2 and roridin A interacted synergistically to inhibit the release rate of CO 2 by K. marxianus at concentrations that the individual toxins did not alter CO 2 release.…”
mentioning
confidence: 99%
“…Towards this end, several unicellular assay systems have been developed to monitor the action of mycotoxins [Buckle and Sanders, 1990;Khachatourians et al, 19891. We have used Kluyveromyces marxianus as a model to develop techniques for studying the action of mycotoxins [Schappert and Khachatourians, 19841 and investigate the interaction between binary mixture of mycotoxins [Koshinsky et al, 1991;Koshinsky and Khachatourians, 1992a,b] toxin and HT-2, or deoxynivalenol (DON), or T2-401, as well as DON and nivalenol using another isolate of K . marxianus in an in vitro bioassay.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective we must include the interactions of mycotoxins [Hesseltine, 1986;Koshinsky and Khachatourians, 19941. Analysis of trichothecene combinations effects in yeast cell bioassays, pioneered by our group [Koshinsky et al, 1991;Koshinsky and Khachatourians, 1992a,b] and extended by Madhyastha et al [1994], have led to new insights on structure-activity correlationships and how mycotoxin combinations interact with cellular targets. We have defined a new term, maximally quiescent ratio (MQR), which is the combination of two compounds at which there is the least variation and lowest intensity in their cellulareffects [Koshinsky and Khachatourians, 1992al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation